2009
DOI: 10.1007/s11113-009-9171-4
|View full text |Cite
|
Sign up to set email alerts
|

Center-Based Care in the Context of One-Child Policy in China: Do Child Gender and Siblings Matter?

Abstract: Center-based care, One-child policy, China, Gender, Sibling,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
9
1
Order By: Relevance
“…The authors did not use household income as a direct predictor in the model and therefore could not make definitive conclusions about the correlation between income and preschool attendance. Using the 2000 wave of CHNS data with a different sample than in our study (0‐ to 6‐year‐old children), Zhai and Gao's () multilevel logistic regression showed that children without siblings, regardless of gender, had a higher chance of attending center‐based care than those with siblings. They also found a slight but significantly positive correlation between household income and center‐based care attendance; however, their study design focused on the association between child gender and the presence of sibling on center‐based attendance.…”
Section: Preschool and Its Financing In Chinacontrasting
confidence: 49%
See 1 more Smart Citation
“…The authors did not use household income as a direct predictor in the model and therefore could not make definitive conclusions about the correlation between income and preschool attendance. Using the 2000 wave of CHNS data with a different sample than in our study (0‐ to 6‐year‐old children), Zhai and Gao's () multilevel logistic regression showed that children without siblings, regardless of gender, had a higher chance of attending center‐based care than those with siblings. They also found a slight but significantly positive correlation between household income and center‐based care attendance; however, their study design focused on the association between child gender and the presence of sibling on center‐based attendance.…”
Section: Preschool and Its Financing In Chinacontrasting
confidence: 49%
“…In China, people living in the same household as a child, such as older siblings or grandparents, often provide child care. A child with older siblings is likely to be taken care of by his or her siblings and less likely to attend preschool (Du & Dong, ; Lehrer, ; Zhai & Gao, ). We thus included a control for the number of school‐aged siblings, measured by the number of children between the ages 6 and 18 in the household.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings also suggest that differentials in parental behaviour across sibship conditions cannot be assumed to explain how children make sense of their own lives. The results therefore problematise the assumption undergirding mainstream policy interventions in China that gender equality among children can be achieved solely by changing the ways in which parents behave and by equalising intergenerational investment (Zhai & Gao, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…These shifts led to considerable yet unintended changes in intergenerational and gender relations in the Chinese family (Kim & Fong, 2014;Tsui & Rich, 2002). A major change, according to many scholars (Fong, 2004;Lee, 2012), was the rise of gender equality among singleton girls who enjoyed unprecedented intergenerational support and investment 'because they do not have to compete with brothers' for resources (Fong, 2002(Fong, : 1098, particularly in urban areas (Xu & Yeung, 2013;Zhai & Gao, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation